Ramadan Fasting in Germany (17–18 h/Day): Effect on Cortisol and Brain-Derived Neurotrophic Factor in Association With Mood and Body Composition Parameters - Riat, Amin; Suwandi, Abdulhadi; Ghashang, Samaneh Khoshandam; Buettner, Manuela; Eljurnazi, Luqman; Grassl, Guntram A.; Gutenbrunner, Christoph; Nugraha, Boya (Frontiers in Nutrition, 2021)
Ramadan fasting (RF) is a type of diurnal intermittent fasting. Previous studies reported the benefits of RF in healthy subjects on mood and health related to the quality of life (QoL). Cortisol and brain-derived neurotrophic factor (BDNF) have been shown to play a role in mood, body composition parameters, and health related QoL. This study aimed at elucidating the mechanism of the benefit of RF, particularly cortisol and BNDF and their association to mood and QoL. Insulin growth factor-1 (IGF-1), interleukin (IL)-8, matrix metalloproteinase (MMP)-9, and myoglobin were determined. Thirty-four healthy male and female individuals were recruited. Serum from peripheral venous blood samples was collected at five time points: one week before RF (T1); mid of RF (T2), last days of RF (T3), one week after RF (T4) and one month after RF (T5). The amounts of biological media-tors in the serum samples were determined by using enzyme-linked immunosorbent assay (ELISA) and luminex assays. BDNF and cortisol significantly decreased at T3 (p<0.05) and T4 (p<0.001) compared to T1, respectively. It seems the benefits of RF for mood-related symptoms are mediated by different biological mediators, particularly cortisol and BDNF.